PERAN GURU PPKN DALAM MENGATASI PERILAKU BULLYING DI SMA NEGERI 1 BONJOL - Lailatul Qoudri; Jaenam; Indra Rahmat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the role of Civic Education teachers in addressing bullying behavior at SMA Negeri 1 Bonjol. The research method used is a qualitative approach with a descriptive method. Data was collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that PPKn teachers act as facilitators and motivators in preventing bullying behavior. Teachers provide an understanding of the impact of bullying, instill the values of Pancasila, and guide students to be tolerant. Challenges faced include limited learning time, lack of student awareness, and the influence of the social environment. In conclusion, PPKn teachers play a crucial role in shaping students' character to prevent bullying behavior, although further support from schools and parents is still needed.